A Case Report and Anesthetic Considerations in Subcutaneous Fat Necrosis of the Newborn. Issue 3 (8th March 2021) - Matar, Marla M.
Abstract : Subcutaneous fat necrosis of the newborn (SCFN) is an uncommon, self-limiting panniculitis generally diagnosed in the first few weeks of extrauterine life in term or postterm infants subjected to perinatal physiologic stress. Hallmarks of the process include dramatic hypercalcemia without identifiable cause that may be associated with renal disease, seizures, and death. Herein, we describe the anesthetic approach in an 11-week-old infant, including perioperative laboratory testing, management of hypercalcemia, and intraoperative considerations.